2021
DOI: 10.21924/cst.6.2.2021.460
|View full text |Cite
|
Sign up to set email alerts
|

Corncob residue as heterogeneous acid catalyst for green synthesis of biodiesel: A short review

Abstract: The utilization of an appropriate catalyst in biodiesel production depends on the free fatty acid content of vegetable oil as a feedstock. Recently, heterogeneous acid catalysts are widely chosen for biodiesel production. However, these catalysts are non-renewable, highly expensive and low stability. Due to the aforementioned drawbacks of commercial heterogeneous acid catalyst, a number of efforts have been made to develop renewable green solid acid catalysts derived from biomass. Published literature revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In the third transesterification, the conversion of the methyl ester obtained decreased. This was because there was a decrease in the active side of the MA-900 catalyst after being used repeatedly [62]. From these results, it can be concluded that the MA-900 catalyst that has been synthesized had an optimum activity after being used for transesterification twice.…”
Section: Usability Test On Ma-900 Catalystmentioning
confidence: 89%
See 1 more Smart Citation
“…In the third transesterification, the conversion of the methyl ester obtained decreased. This was because there was a decrease in the active side of the MA-900 catalyst after being used repeatedly [62]. From these results, it can be concluded that the MA-900 catalyst that has been synthesized had an optimum activity after being used for transesterification twice.…”
Section: Usability Test On Ma-900 Catalystmentioning
confidence: 89%
“…For the purpose of green chemistry, some researches have focused on the exploration and development of new heterogeneous catalysts from renewable sources [17] to add value to them and reduce the environmental pollution they generate when they are burnt as a cheap fuel. Also, catalysts derived from biomass have certain characteristics such as non-toxicity, biodegradability, containing a variety of mineral constituents, surface area, and pore structure that can be tuned [18].…”
Section: Introductionmentioning
confidence: 99%
“…An insignificant enhancement of FFA conversion (85.29±3.2%) was identified after 18 moles of methanol were added to the reaction system. The excess of alcohol in the esterification system at a particular point could dilute the reaction system (Mardina et al, 2021). It could hinder the mass transfer between solid catalysts and reactants.…”
Section: Esterification Reaction Of Waste Cooking Oilmentioning
confidence: 99%
“…It cannot be directly discharged into the environment in view of the high organic matter content and tendency to damage the environment [1,2]. Furthermore, 100 kg of glycerol can be obtained in every ton of biodiesel converted from biomass [1] where biodiesel is an alternative green fuel [3]. Also, glycerol presents a particularly attractive renewable and sustainable source for H2 generation.…”
Section: Introductionmentioning
confidence: 99%